Development of an Individualized Occupational Therapy Programme and its Effects on the Neurocognition, Symptoms and Social Functioning of Patients with Schizophrenia. (17th October 2016) - Shimada, Takeshi; Nishi, Ai; Yoshida, Tomotaka; Tanaka, Sachie; Kobayashi, Masayoshi
Abstract: We described an individualized occupational therapy (IOT) programme and examined the effects of adding IOT to group OT (GOT) on improving neurocognition, symptoms and social functioning among recently hospitalized patients with schizophrenia. The Brief Assessment of Cognition in Schizophrenia—Japanese version (BACS‐J), the Positive and Negative Syndrome Scale (PANSS) and the Global Assessment of Functioning scale were used for outcome evaluations. Fifty‐one patients were voluntarily assigned to either the GOT + IOT ( n = 30) or GOT alone ( n = 21) groups based on their preferences. Retention in the GOT + IOT group was 100%. Three‐month baseline to discharge assessments in the GOT + IOT group showed significant improvements in BACS‐J verbal memory, working memory, verbal fluency, attention, executive function and composite score, and in PANSS positive subscale, general psychopathology subscale, and total score compared to the GOT alone group. Study limitations notwithstanding, the present findings provide preliminary support for the feasibility of implementing IOT and its effectiveness for improving cognitive impairment and symptoms in patients with schizophrenia. The results of this study indicate that IOT in psychiatric facilities may improve psychosocial treatment of schizophrenia. Additional study is warranted to replicate the effects of IOT as demonstrated in this Japanese study. Copyright © 2016 John Wiley & Sons, Ltd.